Arctic Environmental Considerations. - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1972)
The report is intended to assist TECOM agencies and item developers evaluating potential or actual test items by providing basic information on the effects of cold. The information provided is limited to the most common types of material and materiel.